2017
DOI: 10.1136/bmjopen-2016-013501
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing medical students' motivation to practise in rural areas in low-income and middle-income countries: a systematic review

Abstract: ObjectivesThere is a shortage of doctors working in rural areas all over the world, especially in low-income and middle-income countries. The choice to practise medicine in a rural area is influenced by many factors. Motivation developed as a medical student is one key determinant of this choice. This study explores influences on medical students' motivation to practise in rural areas of low-income and middle-income countries following graduation.DesignA systematic review was conducted to identify influences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 48 publications
3
47
1
1
Order By: Relevance
“…6 Studies have shown that early introduction to the rural community and exposure encourages and motivates young graduates to practice there. 5,7,8 But, as observed elsewhere, we anticipate that medical graduates will tend to migrate towards specialised hospital-based training. Despite best of intentions, family, including family parental professional status and career will be the major determinant of where a young graduate chooses to work.…”
Section: Discussionmentioning
confidence: 64%
“…6 Studies have shown that early introduction to the rural community and exposure encourages and motivates young graduates to practice there. 5,7,8 But, as observed elsewhere, we anticipate that medical graduates will tend to migrate towards specialised hospital-based training. Despite best of intentions, family, including family parental professional status and career will be the major determinant of where a young graduate chooses to work.…”
Section: Discussionmentioning
confidence: 64%
“…This contract has an explicit duty to graduate safe doctors to practice in the society, especially if the students are recruited from the same area where the college is located. Incidentally, research has indicated that attracting students from or training of medical students in less developed regions leads to retention of a large number of graduates in those areas as part of the working health force in the future [10,11]. 1 The presence of hospitals and health centers that provide the minimum level of clinical training with a plan to provide advanced training if needed (the goal here is not only buildings but also the number and appropriateness of cases for training, taking into consideration that some practical training may need to be conducted in other social institutions, like social affairs institutions, depending on the type of curriculum being used).…”
Section: Colleges Of Medicine and The Societymentioning
confidence: 99%
“…The financial and academic barriers to admission to medical school tend to favour the selection of students from privileged backgrounds, leading to young doctors who have limited direct experience of the health needs of poor rural and under-served urban communities, with few choosing to serve these communities [12]. Medical students still aspire to become successful in specialist medicine and develop values that are not orientated towards meeting the needs of the poor and disadvantaged in their countries [13]. Whilst there have been some interesting innovative models of health care developed to meet the needs of remote rural populations, such as rural health care development in Quebec and other models pioneered by the Training for Health Equity Network (THE Network) [14], these have yet to be replicated at scale.…”
Section: Introductionmentioning
confidence: 99%